Historical Landslide Fatalities in British Columbia, Canada: Trends and Implications for Risk Management - Strouth, Alex; McDougall, Scott (Frontiers in Earth Science, 2021)
Landslides are the most common type of disaster that occurs in the province of British Columbia according to a Canadian government database. Recently there has been a trend in British Columbia towards using quantitative risk assessments to estimate life-loss risks at landslide hazard sites, and comparing these estimates to risk tolerance thresholds to determine the necessity for, and extent of, risk management measures. These risk estimates are most-often calibrated by so-called ‘expert judgement’ because historical landslide fatality data is not readily available. This article addresses this gap by summarizing available historical data to better inform expert judgement. It shows that fatalities caused by landslides in British Columbia are rare (approximately one fatality per year in the last decade) and have decreased with time despite rapid population growth, likely due to improving risk management practices. Approximately half of these fatalities in the last decade are related to debris flows and debris floods that impact houses, while the other half are related to rockfall, debris flows, and debris floods that impact highways. A comparison with other disaster types in the Canadian government database suggests that, while not particularly deadly, landslides are still important because of the economic damage and service disruptions they cause.